EVALUATION OF OPPORTUNITIES FOR SPECIALIST CONTRACTORS IN THE PROCUREMENT/AUCTION OF CONSTRUCTION SERVICES IN WEST KALIMANTAN - Lusiana, Lusiana (Fakultas Teknik Universitas Tanjungpura, 2022)
The globalization of the construction industry today, as well as its increasing size; novelty; and the complexity of projects is an unavoidable fact. This causes the construction industry to try to increase its capacity in various ways, one of which is by strengthening its construction supply chain. Specialist contractors are part of the supply chain that determines the performance of the main contractor, and ultimately improves the performance of the construction industry.